Typical Lourdes house with no basement. The kitchen, with the woodstove that heats the entire home, is located in the front of the house. - Meaney, Carmelita (1976)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « History of the community of Lourdes and the people that live there ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "History of the community of Lourdes and the people that live there"